A comparison of alfalfa silage and alfalfa hay for wintering heifer calves. - Cathcart, R.B.; Smith, E.F.; Baker, F.H.; Richardson, D.; Cox, R.F. (Kansas Agricultural Experiment Station, 2012)
Forty Texas Hereford heifer calves averaging 360 pounds each were divided into four lots of 10 head each. The feeding test was conducted from December 17, 1953, to April 8. 1954, or 113 days. The alfalfa silage and hay were made from first-cutting feed in the same field, when it was approaching one-half bloom. One lot of silage was preserved with cornmeal at the rate of 150 pounds per ton of green forage. The other silage was made without preservative. Both silages were field-chopped and hauled immediately to the silos. The first feeding plan was to add concentrates to the roughages at the same rate as the corn in the alfalfa-cornmeal silage. However since consumption and gains of all the calves were so unsatisfactory at the end of 29 days of feeding, the plan was altered so that all groups were fed concentrates at the rate of 4 pounds per head daily, allowance being made in Lot 3 for the corn contained in the silage.
Keywords: Beef; Alfalfa silage; Alfalfa hay; Gain